Controllability in oscillation dynamical systems - Ilolov, M.; Elnazarov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider the problem of controllability in oscillation dynamical systems. A solution of the local control problem is obtained for one class of systems of differential equations. An example of application of the main results is given.